The Prognostic Value of Baseline Lymphocyte, Neutrophil, and Monocyte Counts in Locally Advanced Cervical Carcinoma Treated with Radiation - Sareena Singh; Justin Himler; Christa I. Nagel; Kimberly Resnick (Obstetrics and Gynecology International)
Background. To determine the prognostic significance of pretreatment levels of circulating lymphocyte (CLC), neutrophil (CNC), and monocyte (CMC) counts in patients with locally advanced cervical carcinoma (CC) treated with definitive radiation. Methods. A retrospective, dual-institution review of patients with Stage IB2-IVA CC from 2005 to 2015. Progression-free (PFS) and Overall Survival (OS) were determined for high and low CLC, CNC, and CMC groups. Multivariate analysis was used to confirm prognostic value of baseline leukocyte counts. Results. 181 patients were included. Median follow-up time was 26 (3–89) months. CNC had no effect on PFS or OS. PFS was similar between CMC groups; however, OS was significantly improved for patients with low CMC (62.5 versus 45.3 months, p=0.016). High CLC was associated with improved PFS (48.5 versus 27.8 months, p=0.048) and OS (58.4 versus 34.9 months, p=0.048). On multivariate analysis, high CNC was associated with increased relapse risk (HR 1.12, p=0.006) and low CLC was associated with increased mortality risk (HR 0.67, p=0.027). Conclusion. This study demonstrates that leukocyte values can provide prognostic information in CC. These hypothesis-generating findings warrant further prospective investigations.